2021
DOI: 10.11621/pir.2021.0103
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Depression and Birth Experience in Russia

Abstract: Background. In European countries, postpartum depression (PPD) occurs in 13–19% of women. The statistics indicate that postpartum depressive disorders affect up to 300,000 women in Russia annually. There is still an extremely acute lack of psychological comfort provided to women during labor in Russia. Objective. To our knowledge, ours is the first study that examines the association between childbirth experience and the risk of PPD in Russia. Design. We collected data from 190 Russian-speaking mothers, age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
(20 reference statements)
1
15
0
Order By: Relevance
“…One of the factors that may explain this increase is the COVID-19 related restrictions for the presence of support persons during labor. Our previous study showed that women with accompaniment experienced significantly less obstetric aggression in comparison to those giving birth without support [ 12 ]. Another possible factor is burnout of the medical professionals, which increased dramatically during the pandemic [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the factors that may explain this increase is the COVID-19 related restrictions for the presence of support persons during labor. Our previous study showed that women with accompaniment experienced significantly less obstetric aggression in comparison to those giving birth without support [ 12 ]. Another possible factor is burnout of the medical professionals, which increased dramatically during the pandemic [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the strongest effects of the COVID-19 related changes on birth experience is related to the possibility of the support person’s presence during labor. While in the Russian birth culture, the most common situation was hospital birth without any assistance of the partner or birth doula, there was an increasing trend of having a support person during labor [ 12 ]. Our study shows that before the pandemic almost 60% of women had at least one support person with them during labor, while less than 30% could have anyone present at their birth due to the COVID-19 restrictions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a larger comorbidity between PTSD and PND than between PND and PTSD, where most postpartum women with PTSD also present with depression symptoms, while only one in three women with depression symptoms report PTSD symptoms (Dekel et al, 2020;Nakić Radoš et al, 2018). Furthermore, previous studies showed that low birth satisfaction has been related to the higher levels of PND symptoms (Benoit et al, 2007;Blažević et al, 2018;Yakupova & Suarez, 2021). However, these studies used either one item to measure birth satisfaction (e.g., Benoit et al, 2007) or psychometric scales that measure birth satisfaction as a unidimensional construct.…”
mentioning
confidence: 99%
“…However, these studies used either one item to measure birth satisfaction (e.g., Benoit et al, 2007) or psychometric scales that measure birth satisfaction as a unidimensional construct. For example, birth satisfaction was measured with the unidimensional 6-item Birth Satisfaction Scale Revised Indicator (BSS-RI; Martin et al, 2017) in the study by Yakupova and Suarez (2021) or subscale on satisfaction with Delivery and Conduct During Labour from the Childbirth Perception Questionnaire (CPQ; Padawer et al, 1988) in the study by Blažević et al (2018). Indeed, a systematic review established the relationship between negative birth experience and PND in most studies but pointed out the heterogeneity in birth experience instruments (Bell & Andersson, 2016).…”
mentioning
confidence: 99%